Wagner's Meistersinger : Performance, History, Representation - Vazsonyi, Nicholas, 1963- (Book collections on Project MUSE., 2004)
Richard Wagner's "Die Meistersinger von Nürnberg" has been one of the most performed operas ever since its premier in 1868, as it epitomizes themes of Germanness. This volume examines the representation of German history in the opera and the way it has functioned in history through political appropriation and staging practice. in performance.